PELAKSANAAN PROGRAM DOOR TO DOOR SYSTEM DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN KELAPA SAWIT DI WILAYAH HUKUM POLRES KABUPATEN ROKAN HULU - Kifli Raji; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Door to Door System program is one of the programs at the Rokan Hulu Policewhich aims to tackle criminal acts of palm oil theft in the jurisdiction of the Rokan HuluPolice. However, in reality the Door to Door System program is not running effectivelybecause there are several obstacles in its implementation, one of which is a lack of personnelknowledge at the time of implementation and the limited number of personnel inimplementing the Door to Door System program. So the problem formulation in this researchconsists of: 1) how is the Door to Door System Program Implemented in Overcoming theCrime of Palm Oil Theft in the Legal Area of the Rokan Hulu Regency Police, 2) what are theinhibiting factors, and 3) what are the efforts made in Implementation Door to Door SystemProgram. The aims of this research are 1) to find out the implementation of the Door to DoorSystem Program, 2) to find out the inhibiting factors in dealing with criminal acts of palm oiltheft and 3) to find out the efforts made in implementing the Door to Door System Programso that they can be more optimal in dealing with criminal acts palm oil theft.This type of research can be classified as sociological juridical legal research,because this research emphasizes research aimed at gaining knowledge about the door todoor system strategy used by the police in dealing with criminal acts of palm oil theft inRokan Hulu Regency. This research was conducted at the Rokan Hulu Police Station. In thisresearch, the data sources used are primary data and secondary data, data collectiontechniques in this research are observation, questionnaires and interviews.From the results of the research carried out, it can be concluded that, theimplementation of the Door to Door System Program in Overcoming the Crime of Palm OilTheft in the Legal Area of the Rokan Hulu Regency Police through outreach activities to thecommunity, distribution of information, conducting outreach such as raising publicawareness or vigilance, inviting the public to exchange information and also maintain thesecurity and comfort of the community as well as carry out direct monitoring of the fieldwhere the monitoring will be accompanied directly by the community and build activecommunication with the community. Obstacles include a lack of quality personnel and a lackof information. Meanwhile, the efforts made are implementing a rolling personnel model andempowering local wisdom.Keywords: Door to Door System Program, Crim, Palm Oil Theft.